Konseptualisasi Iklim Belajar dan Gaya Belajar dalam Perspektif Pemikiran Islam: Implikasinya terhadap Pengembangan Kreativitas dalam Pendidikan Islam - Maisaroh, Maisaroh; Aqso, andikal; Abdurakhmonovich, Yuldashev Azim; Aqso, andikal; Junaidi, Junaidi (Edukais : Jurnal Pemikiran Keislaman, 2024)
This study aims to analyse the influence of the learning climate and learning styles on students' creativity in Islamic Education. A quantitative approach was employed, using a correlational method. Data were collected through questionnaires measuring the learning climate, learning styles, and student creativity. The sampling technique applied was purposive sampling, with a total of 42 respondents. The data were analysed using multiple linear regression to test the hypotheses.The findings indicate a significant positive influence of the learning climate and learning styles on students' creativity. The regression equation derived is Y = 18.710 + 0.240X1 + 0.269X2. The T-test results show that both the learning climate (X1) and learning styles (X2) contribute significantly to student creativity (Y). The Adjusted R Square value of 0.148 indicates that 14.8% of the variation in student creativity is explained by the learning climate and learning styles. Meanwhile, the remaining 85.2% is influenced by other factors not included in this research.